T cells at the site of autoimmune inflammation show increased potential for trogocytosis. - Bettina Haastert; Richard J Mellanby; Stephen M Anderton; Richard A O'Connor (PLoS ONE)
CD4+ T cells acquire membrane fragments from antigen-presenting-cells via a process termed trogocytosis. Identifying which CD4+ T cells undergo trogocytosis in co-culture with Ag-loaded APC can enrich for antigen-reactive T cells without knowledge of their fine specificity or cytokine-production profiles. We sought to assess the suitability of this method to identify disease relevant effector and regulatory T cells during autoimmune inflammation. Trogocytosis efficiently identified MBP-reactive T cells in vitro and ex-vivo following immunization. However, Foxp3+ regulatory T cells constitutively displayed a higher rate of trogocytosis than their Foxp3- counterparts which limits the potential of trogocytosis to identify antigen-reactive Treg cells. During inflammation a locally elevated rate of trogocytosis (seen in both effector and regulatory T cells isolated from the inflamed CNS) precludes the use of trogocytosis as a measure of antigenic reactivity among cells taken from inflammatory sites. Our results indicate trogocytosis detection can enrich for Ag-reactive conventional T cells in the periphery but is limited in its ability to identify Ag-reactive Treg or T effector cells at sites of inflammation. Increased trogocytosis potential at inflammatory sites also draws into the question the biological significance of this phenomenon during inflammation, in Treg mediated suppression and for the maintenance of tolerance in health and disease.